Anomali Kewenangan Mahkamah Konstitusi ditinjau dari Teori Separation of Power Montesquieu: Studi Kasus Putusan Mahkamah Konstitusi No.90/PUU-XXI/2023 - Atmaja Wijaya; Didan Neofal Arsyandi (UIN Sunan Kalijaga Yogyakarta, 2024)
The Constitutional Court, as one of the highest judicial institutions in the judicial sector, is given the authority to control the running of government, in the form of overseeing legal products made by other branches of power, namely, the Executive and the Legislative. However, as time goes by, after 20 years of post-reformation, the existence of the Constitutional Court now often attracts a lot of attention with dynamics that are increasingly occurring day by day. Through several of its decisions, there are indications that the Constitutional Court has exceeded its authority as a judicial institution. One of them is in the Constitutional Court decision No. 90/PUU-XXI/2023. This makes it interesting to examine whether there are anomalies in the authority of the Constitutional Court in handling cases, especially in case No.90/PUU-XXI/2023 in terms of Montesquieu's theory of separation of power. The results obtained are that the Constitutional Court has exceeded its authority in making decisions, has violated the limits of authority granted by law and is contrary to the principles of Montesquieu's theory Separation of power. Abstrak: Mahkamah Konstitusi sebagai salah satu lembaga kekuasaan kehakiman tertinggi di bidang Yudikatif, diberikan kewenangan untuk mengontrol jalannya pemerintahan, dengan upaya mengawal produk hukum yang dibuat oleh cabang kekuasaan lain yaitu, Eksekutif dan Legislatif. Namun seiring berjalannya waktu, setelah 20 tahunan pasca reformasi, keberadaan Mahkamah Konstitusi kini kerap banyak menuai sorotan dengan dinamika bertambahnya putusan-putusan yang kontroversial. Melalui beberapa putusannya, terdapat indikasi bahwa Mahkmah Konstitusi telah melampaui kewenangannya sebagai lembaga Yudisial. Salah satunya dalam putusan MK No 90/PUU-XXI/2023. Hal tersebut menjadi menarik untuk diteliti, apakah terdapat anomali kewenangan Mahkamah Konstitusi dalam menangani perkara, khususnya pada perkara No.90/PUU-XXI/2023. Anomali dalam Putusan tersebut, menarik untuk ditinjau dengan teori pembagian kekuasaan (Separation of Power) Montesquieu. Hasil yang diperoleh dari penelitian ini menunjukkan bahwa Mahkamah Konstitusi telah melampaui kewenangannya dalam memberikan keputusan, menabrak batas kewenangan yang telah diberikan Undang-undang dan bertentangan dengan prinsip teori pembatasan kekuasaan Montesquieu